An Alternative Technical Education System in Mexico : A Reassessment of CONALEP - Lopez-Acevedo, Gladys (World Bank, Washington, DC, 2014)
Using matched pair methods, Lopez-Acevedo reevaluates the labor market performance of graduates of Mexico's Colegio Nacional de Educacion Profesional Ttnica (CONALEP), the country's largest technical education system. She also assesses the impact of innovations introduced by CONALEP in 1991. The analysis shows that individuals in the control group find jobs faster than CONALEP graduates do, but a larger share of CONALEP graduates work in an occupation consistent with their field of specialization or training. CONALEP graduates earn 20-28 percent more than the control group. And employers invest more in training CONALEP graduates than they do in training individuals in the control group. The author shows that the innovations introduced by CONALEP increase graduates' probability of finding a job and shorten their job search. A cost-benefit analysis appears to show that CONALEP is an effective training system.